Nodule damage by clover root weevil larvae in white clover swards - Gerard, P.J. (New Zealand Plant Protection, 2002)
The impact of clover root weevil larval populations was assessed in pure swards of Grasslands Prestige and Grasslands Kopu white clover in a small plot trial Nodule damage was very evident and both cultivars showed significant increases in nodule damage and decreases in percent foliar nitrogen in November in response to increasing winter larval numbers Dry matter production of Kopu in November was related to foliar nitrogen levels